Raspberry Pi-Based Farming Automation and Monitoring System using Automatic Weather System (AWS) (Case Study: Chili Plants) - Rohadi, Erfan; Admiral Abdurrahman, Raka; ., Ekojono; Andrie Asmara, Rosa; Siradjuddin, Indrazno; Ronilaya, Ferdian; Setiawan, Awan (International Journal of Engineering and Technology, 2018)
Recently, The Internet of Things (IoT) has been implemented and become an interesting topic for discussion. IoT is a method that aims to maximize the benefits of Internet connectivity to transfer and process data or information through an internet network wirelessly, virtual and autonomous. One of the IoT's utilization is automation system. The automation system generally uses a timer for the plant watering process. The use of timers aims to water the plants routinely without human assistance. The development of this automation system begins with the making of the prototype of chili land in the field 5 x 2.5 meters, then compile the required components and how it works. Further programming of sensors to Raspberry Pi as a controller in the system based on the conditions that have been set and changes in temperature received by the sensor. As a result, the system has been successfully done automatic watering, both on a regular basis (at 06.00 and 18.00) and cooling watering. Cooling is done if the temperature exceeds more than 30 degrees Celsius. The automation system promises to be applied to the utilization of land around the house.Â Â